Improving On-time Discharge in Otolaryngology Admissions. (August 2020) - Gordon, Steven A.; Garber, David; Taufique, Zahrah; Shao, Qianhui; Amin, Milan R.; Roland, J. Thomas; Givi, Babak
Objective: We conducted a quality improvement project to increase the rate of discharges before noon (DBN) in the otolaryngology department at a tertiary care center. Methods: Based on a Plan-Do-Study-Act framework, monthly discharge data and observed-to-expected (O:E) length of stay were collected and shared with the department members monthly. A target of 43% DBN was predetermined by the center (Plan). The following interventions were implemented (Do): discharge planning starting at the time of admission, focus on early attending-to-resident team communication, placement of discharge order prior to rounding, and weekly reminders to the entire department. Results: Discharges were monitored for 3 years. For the year prior to this study, a minority of patients were discharged before noon (12 months: 75 of 190, 36%). During the first 6 months of monitoring (Study), no significant improvement was identified (34 of 95, 36%). After interventions, performance significantly improved (31 months: 250 of 548, 68%). The performance was consistently above the predetermined target of 43%. During the study time, O:E length of stay remained below the predetermined target (O:E ratio, 0.90; hospital target, 0.93). Discussion: Comprehensive discharge planning beginning at the time of admission, weekly reminders, and improved communication (Act) can help to prioritize DBN and increase the percentage of discharges before noon. Implications for Practice: By utilizing a quality improvement framework, significant improvements in timely discharge can be achieved and sustained with changes in workflow and departmental culture. These changes can be achieved without increases in resources or prolonging the length of stay.